2013
DOI: 10.1007/s13224-012-0332-8
|View full text |Cite
|
Sign up to set email alerts
|

LLETZ Specimen Fragmentation: Impact on Diagnosis, Outcome, and Implications for Training

Abstract: Purpose This study was designed to assess fragmentation of Large loop excision of the transformation zone (LLETZ) specimens, its influence on short-term cytological outcome, and the risk factors for specimen fragmentation, as we well as trainee performance on clinical outcome. Method This retrospective study was performed at a cancer center. Women who underwent LLETZ for suspected high-grade cervical intra-epithelial neoplasia (CIN) over a 5-year period were included. Patients were identified through a regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…It should be considered that residual disease is more frequent in women with positive margin status 16,17 . Although LLETZ technique is superior in many ways to other excisional techniques, some reports claim that thermal artifacts and specimen fragmentation can have negative impact on histopathologic interpretation 18,19 . According to the National Health Service Cervical Screening Programme (NHS-CSP) standards from the United Kingdom, at least 80% of the specimens obtained by LLETZ technique should be in single form 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It should be considered that residual disease is more frequent in women with positive margin status 16,17 . Although LLETZ technique is superior in many ways to other excisional techniques, some reports claim that thermal artifacts and specimen fragmentation can have negative impact on histopathologic interpretation 18,19 . According to the National Health Service Cervical Screening Programme (NHS-CSP) standards from the United Kingdom, at least 80% of the specimens obtained by LLETZ technique should be in single form 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Adequate histological interpretation of the LLETZ specimen requires complete assessment of the margins. Literature data suggest that several patient and surgeon characteristics may influence sample adequacy [3]. Patient related factors include habitus, relaxation and vaginal compliance, age, parity, indication for the surgery and morphology and grade of the disease.…”
Section: Histology and Margin Status Of Specimensmentioning
confidence: 99%
“…Messing et al [8] evaluated the specimens obtained by residents and found that 26.09 % of them had severe thermal artifacts precluding the evaluation for both the grade of dysplasia and the margins. Thermal artifacts are determined by the loop size, speed of cutting, electrical energy and tissue conductivity [3,8,17]. In cases of repeated excisions, artifacts are present on all sides of the specimens, except on the ectocervical surface [8].…”
Section: Histology and Margin Status Of Specimensmentioning
confidence: 99%
See 2 more Smart Citations